Local Potential-Based Development as a Strategy to Enhance Economic and Social Welfare - Harahap, Muhammad Ade Kurnia; Almaududi Ausat, Abu Muna; Azzaakiyyah, Hizbul Khootimah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Local potential-based development is a strategic approach aimed at improving economic and social welfare through the optimization of local resources. This study examines the implementation of local potential-based development across various regions in Indonesia, focusing on the challenges, opportunities, and impacts it generates. The research utilizes a qualitative approach and descriptive analysis of 14 selected articles from an initial 30 articles retrieved from Google Scholar for the 2011-2024 period. The findings indicate that local potential-based development in sectors such as tourism in Banyuwangi, agribusiness in Garut, and renewable energy in West Sumatra significantly contributes to increased community income, job creation, and preservation of local culture. However, success in these initiatives requires adequate infrastructure, supportive policies, and collaboration among government, communities, and the private sector. This study provides essential insights for policymakers and stakeholders in designing sustainable and inclusive development programs.